Research Mapping on Distributed Energy Systems Using Renewable Energy - Handrea Bernando Tambunan; Agussalim Syamsuddin; Natalina; Mujammil A. Rahmanta; Fefria Tanbar; Wigas Digwijaya; Acmed Nurfanani (Universitas Nusa Putra, 2023)
The availability of energy is essential to support modern human activities worldwide, pushing global energy consumption to an unprecedented level within the last century. Several aspects, such as population, economy, greenhouse gas emissions (GHG) emission, gross domestic product, and labor growth, have a favorable relationship with energy consumption, which means an enlargement in energy consumption. On the other hand, distributed energy systems (DES) and renewable energy (RE) are popular alternative sources of energy production as part of the energy mix toward energy security and sustainability to tackle environmental issues. This paper aims to analyze and review the research trend of DES and RE in recent decades through bibliometric tools. Thus, the study addressed the following research questions: worldwide research’s prominent authors, relevant sources, the word associated with this research field, and thematic analysis through the Scopus database and Bibliohiny R-package. This work can help the academicians, researchers, and scientific community comprehend the study fields more rapidly.